Developing students' leadership character at the Madinatunnajah Islamic Boarding School in South Tangerang: The program and organizational strategy of Madinatunnajah's students - Rohim, Muhamad; Mutiara, Diah (Kepompong Children Centre Journal, 2024)
The leadership character students possess aims to cultivate wise individuals who are devout to Allah, possess noble morals, and demonstrate fairness, honesty, discipline, responsibility, professionalism, loyalty, and other positive traits. Within the activities conducted in the Islamic school (madrasah), the student organization of Madinatunnajah Islamic Boarding School serves as a platform for shaping the leadership character of students. This research aims to ascertain: 1) The programs implemented to foster leadership character among male students within the Student Organization of Madinatunnajah. 2) The strategies employed to develop leadership character among male students through the Student Organization of Madinatunnajah. 3) How do Madinatunnajah Islamic Boarding School students demonstrate their character through the Madinatunnajah Student Organization? 4) Supporting and inhibiting factors in shaping the leadership character of students within the Madinatunnajah Student Organization. The research methodology used is qualitative. The results of this study indicate that the programs and organizational strategies of Madinatunnajah students in shaping the leadership character of male students at the Madinatunnajah Islamic Boarding School are as follows: 1) The programs implemented include annual activities and incidental activities, such as PORSEKA, organizational activities, pilgrimage to the Walisongo sites, and PPM (Community Service Practice). 2) The strategy is through applying Uswatun Hasanah or good role models. 3) The character of Madinatunnnajah students is good, as seen in every activity conducted by the students. 4) The supporting factor is the support from the entire board of boarding school teachers, parents, and friends, while the inhibiting factors are oneself and the family environment.